INVESTMENT ATTRACTION THE DEVELOPMENT OF PEAT DEPOSITS ON THE EXAMPLE OF LENINGRAD REGION - Galina Peshkova (Вестник Северо-Кавказского федерального университета, 2022)
In the artikle presetet large number of unclaimed deposits ofpeat dictate the necessity to intensify their input in industrial development. Moreover, the scope of use ofpeat is very diverse and importantfor the regional economy in such branches as: small power, construction, agriculture, medicine, as well as for the development of environmental technologies. Research objective: development of criteria for selecting the most perspective peat deposits of undistributed subsoil fund by infrastructure and quality parameters for subsequent economic assessment and determine the most attractive investment objects. Results: the study identified a wide range of the use of peat and products of processing; the main areas of peat use are energy, agriculture, medicine, chemical industry, construction. It is established that in the Leningrad region has a huge resource potential of peat deposits, the amount of open and undeveloped deposits over 1700. A list of criteria for the selection ofpeat deposits for development, including the status of land use, resources and availability of transport infrastructure, qualitative characteristics of peat is developed. A list of the 10 most attractive investments of peat deposits of the Leningrad region is presented. Economic assessment of peat development and calculation of budget and commercial eficiency are made.